(untitled) (Journal-of-Ethiopian-Church-Studies/የኢትዮጵያ-ቤተ-ክርስቲያን-ጥናት-መጽሔት-Live, 2018)
Bahire Hasab is one of the most widely accepted numeracy studies among Ethiopian scholars. This study identifies the cycles of the sun, moon, stars, and winds and their longevity. Through these cycles, it is used to count the ages, to calculate the time of some past and future events. The Ethiopian calendar dates back to creation. The purpose of the study is to show that the book of Enoch is the source of the study of astronomy and its relevance to astronomy, astronomy, and meteorology. The main book used by Ethiopian scholars for various natural research is the Book of Enoch. Thus, the book of Enoch is based on the Ethiopian calendar, philosophy, and theology. To prove this, the study was conducted using a variety of written evidence and interviews with experts. The results of the study show that the Ethiopian calendar is based on the importance of the sun, moon, and stars; Higher education in modern science, especially in Algebra & amp; Trigonometry ”is also an indigenous art that demonstrates the ability to do research without the need for word processing. In addition, we have studied the ancient curriculum in Ethiopia and the society's great philosophical arts in chronology, astronomical studies, astrology, weather forecasting, and meteorology and climate studies